3D impurity profiles of doped/intrinsic amorphous-silicon layers composing textured silicon heterojunction solar cells detected by atom probe tomography. (3rd December 2020) - Shimizu, Yasuo; Han, Bin; Ebisawa, Naoki; Ichihashi, Yoshinari; Hashiguchi, Taiki; Katayama, Hirotaka; Matsumoto, Mitsuhiro; Terakawa, Akira; Inoue, Koji; Nagai, Yasuyoshi
Abstract: Laser-assisted atom probe tomography was used to identify the impurity distribution in Si heterojunction (SHJ) solar cells composed of thin doped/intrinsic amorphous Si layers on the textured surface of a crystalline Si wafer. A site-specific lift-out technique involving a focused ion beam enabled the selection of a ∼2 × 2  μ m 2 area on an arbitrary pyramidal surface. The distributions of B, P and C in the amorphous Si layers introduced by p -type (trimethyl-borane or diborane) or n -type (phosphine) dopant gases were investigated. Standard guidelines for the assessment of the H content in amorphous Si of SHJ solar cells were provided.